Development and validation of an HPLC method for the quantitation of 1,3-dihydroxy-2-methylxanthone in biodegradable nanoparticles - Maribel Teixeira (2008)
A rapid and simple high-performance liquid chromatographic method for the analysis of 1,3-dihydroxy-2-methylxanthone (DHMXAN) in biodegradable poly(D,L-lactide-co-glycolide) (PLGA) nanosphere and nanocapsule formulations is developed and validated. The method does not require any complex sample extraction procedure. Chromatographic separation is made with a reversed-phase C18 column, using methanol-water (90:10, v/v) containing 1% (v/v) acetic acid as a mobile phase at a flow rate of 1 mL/min. Identification is made by UV detection at 237 nm. The isocratic system operates at ambient temperature and requires 7.5 min of chromatographic time. The developed method is statistically validated according to ICH guidelines and USP 29 for its specificity, linearity, accuracy, and precision. The assay method proposed in this study is specific for DHMXAN in the presence of nanosphere and nanocapsule excipients. Diode-array analyses confirm the purity of DHMXAN peak in stress conditions (> 99.0%). The method is shown to be linear (r 0.999) over the concentration range of 0.25-3.0 g/mL. Recovery ranges from 99.0% to 102.7% (RSD: 1.49%) and from 98.3% to 101.6% (RSD: 1.07%) for nanospheres and nanocapsules, respectively. Repeatability (intraassay precision) and intermediate precision is acceptable with RSD values ranging from 0.6% to 1.9% and from 0.3% to 2.0%, respectively. The method is shown to be suitable for the evaluation of DHMXAN content entrapped in PLGA nanoparticles.